Corporate Takeovers In Malaysia: Discriminant Analysis For Bidder And Target Firms - Ali, Ruhani; G. S. Gupta, G. S. Gupta (Asian Academy of Management (AAM), 2000)
This study provides an explanatory model for the takeover selection process in Malaysia using 144 non-fmancial firms, which includes bidders, targets, control bidders and control targets for period 1980-1993. The takeover firms are first analyzed on a univariate basis to assess the differences in the bidder and target groups to examine if the bidder firms were more efficient than the target firms were. The discriminant model that provides a useful tool for explaining the categorical classification is then used for delineating the bidder and target firms. A set of five economic/financial variables has been identified to discriminate between the firm’s groupings using publicly available time series data. The empirical findings suggest that; a) five predictive variables account for about 90% of the firms’ groupings, b) fmancial leverage is the most powerful discriminatory variable followed by profit, risk, size, and growth, in that order, c) bidder firms have higher profit and growth, and lower leverage, risk and size, than the target firms, and accordingly provide some support that, d) the takeover was motivated by the bidder firms’ desire for reaping the fruits of economies of scale in order to maintain the tempo of high profit and high growth and/or for displacement of inefficient managers of target firms. The accuracy of the results is shown to hold using the logistic regression model.